Brazil's Secondary School Crisis and Its Victims - Maria Helena Guimarães Castro; Haroldo da Gama Torres; Danilo França (Universidade de Lisboa, 2013)
Public secondary schools continue to be uninspiring and often disorganized, unsafe places. This article looks specifically at the issue of Brazil´s secondary school education, which is showing clear signs of stagnation in terms of coverage and quality. Only half of Brazil´s young people aged 15 to 17 attend secondary school and the proportion of students dropping out of school has doubled over the last ten years. Those who neither work nor study account for 24 % of 18 year-olds and 25 % of 20 year-olds. Furthermore, the majority of those who neither study nor work come from households with incomes of under 2 minimum wages. Addressing this issue involves inter alia revising of the curriculum, integrating secondary with vocational education and introducing policies to diversify secondary education.